2018
DOI: 10.1007/s11869-018-0651-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of roadside vegetation characteristics on local, near-road air quality

Abstract: Roadside vegetation has been shown to impact downwind, near-road air quality, with some studies identifying reductions in air pollution concentrations and others indicating increases in pollutant levels when vegetation is present. These widely contradictory results have resulted in confusion regarding the capability of vegetative barriers to mitigate near-road air pollution, which numerous studies have associated with significant adverse human health effects. Roadside vegetation studies have investigated the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…Given that the LAD of most naturally occurring vegetation is 1-5 m 2 /m 3 102 , and in line with findings by Ghasemian et al 54 , a LAD of~4 m 2 /m 3 may be recommended. Indeed, such a value would be in agreement with recent findings from CFD modelling undertaken by Deshmukh et al 53 , which suggested that a LAD of 3 m 2 /m 3 or higher is needed for downwind PM reductions. However, it should be noted that the density of a species that forms part of a barrier under active management may differ considerably from that exhibited by the same species under 'natural' or comparatively unmanaged conditions.…”
Section: Density and Porositysupporting
confidence: 91%
See 1 more Smart Citation
“…Given that the LAD of most naturally occurring vegetation is 1-5 m 2 /m 3 102 , and in line with findings by Ghasemian et al 54 , a LAD of~4 m 2 /m 3 may be recommended. Indeed, such a value would be in agreement with recent findings from CFD modelling undertaken by Deshmukh et al 53 , which suggested that a LAD of 3 m 2 /m 3 or higher is needed for downwind PM reductions. However, it should be noted that the density of a species that forms part of a barrier under active management may differ considerably from that exhibited by the same species under 'natural' or comparatively unmanaged conditions.…”
Section: Density and Porositysupporting
confidence: 91%
“…For example, highly porous (lowdensity) vegetation barriers can reduce wind speed as it penetrates gaps, potentially resulting in pollutant accumulation downwind (i.e. within and beyond the barrier) 34,53 . Conversely, very low-porosity vegetation can limit pollution removal by restricting infiltration and forcing air pollutants to flow above and around the barrier or to recirculate and accumulate on the upwind or source side 29,54 .…”
Section: Local Scalementioning
confidence: 99%
“…injuries). Second, vegetation can reduce air pollution (Deshmukh et al, 2019;Przybysz et al, 2019). This may be a modi er regarding the effect of regional air pollution on dementia mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile monitoring utilized an instrumented electric vehicle recording 1-s ultrafine particulate matter number count (UFP), black carbon (BC), nitrogen dioxide (NO 2 ), and carbon dioxide (CO 2 ) data. Mobile monitoring used a combination of the Geospatial Monitoring of Air Pollution (GMAP) electric vehicle (Ford Focus) and a stationary sport utility vehicle (SUV; Ford Excursion) outfitted with fast-response air monitoring instruments which have been employed in previous studies [14]. The vehicles have separate, onboard solar and battery supplies powering the air monitoring instruments.…”
Section: Kc-traqs Field Studymentioning
confidence: 99%